Peptidyl-tRNA hydrolase from Sulfolobus solfataricus - Fromant, Michel (Oxford University Press, 2003)
An enzyme capable of liberating functional tRNA(Lys) from Escherichia coli diacetyl-lysyl-tRNA(Lys) was purified from the archae Sulfolobus solfataricus. Contrasting with the specificity of peptidyl- tRNA hydrolase (PTH) from E.coli, the S.solfataricus enzyme readily accepts E.coli formyl-methionyl-tRNA(fMet) as a substrate. N-terminal sequencing of this enzyme identifies a gene that has homologs in the whole archaeal kingdom. Involvement of this gene (SS00175) in the recycling of peptidyl-tRNA is supported by its capacity to complement an E.coli strain lacking PTH activity. The archaeal gene, the product of which appears markedly different from bacterial PTHs, also has homologs in all the available eukaryal genomes. Since most of the eukaryotes already display a bacterial-like PTH gene, this observation suggests the occurrence in many eukaryotes of two distinct PTH activities, either of a bacterial or of an archaeal type. Indeed, the bacterial- and archaeal-like genes encoding the two full-length PTHs of Saccharomyces cerevisiae, YHR189w and YBL057c, respectively, can each rescue the growth of an E.coli strain lacking endogeneous PTH. In vitro assays confirm that the two enzymes ensure the recycling of tRNA(Lys) from diacetyl-lysyl-tRNA(Lys). Finally, the growth of yeast cells in which either YHR189w or YBL057c has been disrupted was compared under various culture conditions. Evidence is presented that YHR189w, the gene encoding a bacterial-like PTH, should be involved in mitochondrial function.